Guidance and management techniques help to combat and recover from Fall ArmyWorm in West and Central Africa - CGIAR Research Program on Maize (2020)
On the basis of a comprehensive integrated pest management (IPM) approach to control fall armyworm (FAW; spodoptera frugiperda), MAIZE convened west and central African partners, who incorporated the approach in policy & extension systems. It focuses on the use of 6 promising indigenous parasitoids and screening of different chemical pesticides, biopesticides and botanicals. Under good agronomic management, their use led to good maize recovery. Promising synthetic varieties have been developed and currently tested in on-farm trials to fast-track their commercialization.